ChemInform Abstract: Synthetic Tuning of Electronic and Photophysical Properties of 2‐Aryl‐1, 3‐Benzothiaphospholes. Issue 51 (17th December 2013) - Worch, Joshua C.; Chirdon, Danielle N.; Maurer, Andrew B.; Qiu, Yunyan; Geib, Steven J.; Bernhard, Stefan; Noonan, Kevin J. T.
Abstract A new method to produce the title compounds albeit in low yields is presented.